2019
DOI: 10.3390/ijerph16183351
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Government, Enterprise, and Public in Environmental Governance from the Perspective of Multi-Player Evolutionary Game

Abstract: Environmental governance is an important component of the national governance system. China’s current environmental problems are particularly complex. How to let the government, enterprises, and the public participate in environmental governance is the key to enhance the ability of environmental governance. Based on the evolutionary game theory, the interaction and influencing factors among enterprise pollution control, government supervision, and public participation are analyzed, and the empirical analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 32 publications
(28 reference statements)
0
45
0
Order By: Relevance
“…After a single game, the subject would not withdraw from the social group. Therefore, the heterogeneous subjects would, in the process of the game, continue to learn, try, and make mistakes instead of making one-time choice [40], find the optimal strategy under the influence of social network structure, and then form the inherent evolutionary pattern of the diffusion of decision-making. We used the small-world network structure in a complex network to metaphorize a social network in which relatives and friends exchange information in a social environment [41,42].…”
Section: Evacuate Staymentioning
confidence: 99%
“…After a single game, the subject would not withdraw from the social group. Therefore, the heterogeneous subjects would, in the process of the game, continue to learn, try, and make mistakes instead of making one-time choice [40], find the optimal strategy under the influence of social network structure, and then form the inherent evolutionary pattern of the diffusion of decision-making. We used the small-world network structure in a complex network to metaphorize a social network in which relatives and friends exchange information in a social environment [41,42].…”
Section: Evacuate Staymentioning
confidence: 99%
“…Ruiz-Villaverde et al [34] identified several advantages of public and stakeholder participation in water management, such as the better use of knowledge and experiences from different stakeholders, increases in public acceptance, and reduced litigation, delays, and inefficiencies in implementation. Chen et al [35] pointed out that government supervision has a positive effect on environmental governance and can urge enterprises to actively perform pollution control. The effect of government supervision is constrained by the income and costs of enterprises, and the penalties for passive pollution control should be raised.…”
Section: Public Participation In Natural Hazard Emergency Reliefmentioning
confidence: 99%
“…Lan et al used evolutionary game theory to investigate the various factors which influence the strategy selection of the parties in school sports injury accidents [ 42 ]. Chen et al discussed the interaction and influencing factors among enterprise pollution control, government supervision and public participation [ 43 ]. Moreover, evolutionary game theory is also used in the treatment and diagnosis of diseases.…”
Section: Literature Reviewmentioning
confidence: 99%